„O zachowaniu się przy stole”, czyli językowa kreacja obyczajów biesiadnych w "Krzyżakach" Henryka Sienkiewicza - Mariak, Leonarda (Wydawnictwo "Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2010)
The present article contains a linguistic and stylistic analysis of the presentation of table manners and table etiquette as it is described in "Krzyżacy" [The Knights of the Cross] by Henryk Sienkiewicz. The article consists of three parts which successively describe the most important elements of medieval cuisine (courses, beverages and spices). Some attention has also been paid to the dishes and good manners at the table. The analysis of the collected lexical material shows that the festive manners, courses, beverages and dishes presented in the novel complete the credibility of other realities of medieval everyday life described in the novel, such as clothes, furnishings of Medieval houses and entertainment. Taking into account the minimal number of historical sources dedicated to everyday life of Medieval Polish people, the world of festive manners and the cuisine created by Henryk Sienkiewicz, which is close to medieval reality, came into existence mainly thanks to the writer’s imagination and language intuition.
"On the manners to be observed at meals", or the linguistic creation of festive manners and cuisine in "Krzyżacy" by Henryk Sienkiewicz
Keywords: Leksyka kulinarna; Leksyka biesiadna; Powieść historyczna; Henryk Sienkiewicz